Epidemiology and outcomes of vancomycin-resistant enterococcus infections: a systematic review and meta-analysis - Eichel, Vanessa; Last, K.; Brühwasser, C.; von Baum, H.; Dettenkofer, M.; Götting, T.; Grundmann, H.; Güldenhöven, H.; Liese, J.; Martin, M.; Papan, C.; Sadaghiani, C.; et al. (The journal of hospital infection, 2023)
Vancomycin-resistant enterococci (VRE) cause many infections in the healthcare context. Knowledge regarding the epidemiology and burden of VRE infections, however, remains fragmented. We aimed to summarize recent studies on VRE epidemiology and outcomes in hospitals, long-term-care facilities (LTCFs) and nursing homes worldwide based on current epidemiological reports. We searched MEDLINE/PubMed, the Cochrane Library, and Web of Science for observational studies, which reported on VRE faecium and faecalis infections in in-patients published between January 2014 and December 2020. Outcomes were incidence, infection rate, mortality, length of stay (LOS), and healthcare costs. We conducted a meta-analysis on mortality (PROSPERO registration number: CRD42020146389). Of 681 identified publications, 57 studies were included in the analysis. Overall quality of evidence was moderate to low. VRE incidence was rarely and heterogeneously reported. VRE infection rate differed highly (1-55%). The meta-analysis showed a higher mortality for VRE faecium bloodstream infections (BSIs) compared with VSE faecium BSIs (risk ratio, RR 1.46; 95% confidence interval (CI) 1.17-1.82). No difference was observed when comparing VRE faecium vs VRE faecalis BSI (RR 1.00, 95% CI 0.52-1.93). LOS was higher in BSIs caused by E. faecium vs E. faecalis. Only three studies reported healthcare costs. In contrast to previous findings, our meta-analysis of included studies indicates that vancomycin resistance independent of VRE species may be associated with a higher mortality. We identified a lack of standardization in reporting outcomes, information regarding healthcare costs, and state-of-the-art microbiological species identification methodology, which may inform the set-up and reporting of future studies.
Online verfügbar 19 September 2023, Version des Artikels 12 October 2023
Gesehen am 17.05.2024